Frequency of pathogenic/likely pathogenic germline variants in cancer‐related genes among children with acute leukemia in Saudi Arabia. Issue 7 (2nd May 2020) - Alsultan, Abdulrahman; Essa, Mohammed; Aljefri, Abdullah; Ayas, Mouhab; Alharbi, Musa; Alkhayat, Nawaf; Al‐Anzi, Faisal; Yassin, Fawwaz; Alkasim, Fawaz; Alharbi, Qasim; Abdullah, Shaker; Jastaniah, Wasil
Abstract: Background: The frequency of pathogenic/likely pathogenic (P/LP) germline mutations in cancer‐related genes among children with cancer in highly consanguineous populations is not well studied. Methods: Whole‐exome sequencing of germline DNA was performed in 60 children with acute leukemia. We used the St. Jude Pediatric Cancer Variant Pathogenicity Information Exchange (PeCanPIE) data portal for the classification of germline variants by the St. Jude Medal Ceremony pipeline. Results: Fifty‐seven patients had acute lymphoblastic leukemia (ALL) and three patients had acute myeloid leukemia. Parental consanguinity was present in 27 (45%) patients. All patients were of Arab ancestry. Three patients (5%) had a history of cancer in their siblings. Five patients (8.3%) had P/LP germline mutations in cancer‐related genes. Three patients with B‐ALL had heterozygous pathogenic mutations in TP53, BRCA1, and BRCA2 ; one patient with B‐ALL had homozygous pathogenic mutation in PMS2 ; and one patient with T‐ALL had LP homozygous mutation in AK2 that was associated with reticular dysgenesis. Among patients who had history of parental consanguinity, three (11%) had P/LP germline mutations compared with two (8%) in the absence of parental consanguinity. Fourteen (23%) patients had gold medal variants in cancer‐related genes, 13 were heterozygous, and one was homozygous. Silver medal variants were present in 35 (58%) patients; all were heterozygous except one homozygous. Conclusions: Children with acute leukemia in Saudi Arabia had low frequency of P/LP mutations in cancer‐related genes despite the high rate of consanguinity. Larger studies using whole‐genome sequencing are needed to further explore the heritability of childhood leukemia.